Let's analyze Kamal's equation step by step:
The equation given is:
\[ 3(x - 8) = x + 2x + 7 \]
First, simplify the right side:
\[ x + 2x + 7 = 3x + 7 \]
So, rewrite the equation:
\[ 3(x - 8) = 3x + 7 \]
Next, simplify the left side:
\[ 3x - 24 = 3x + 7 \]
Now, subtract \( 3x \) from both sides:
\[ -24 = 7 \]
This statement is not true, which implies that there is no value of \( x \) that will satisfy the equation. Therefore, the solution to Kamal's equation is that there is no solution.
So the answer is no solution.